Argicultural Land Tidal Swamp and Development Strategy Era of Regional Autonomy - AR RIZA, ISDJANTO; ALKASUMA, . (Jurnal Sumberdaya Lahan, 2008)
Swamp land is one of natural resources which must be utilized wisely. Swamp land is able to be a growth resource that supports economic development and people welfare. In the autonomy era which has delegated a large authority to the regency administration, however, the tidal swamp land management has to consider the specific of land properties and characteristics. Land use policy should not be performed through a number of activities which can cause dramatically changes that has negative impact to environment qualities in the entire swamp system in the area. Swamp land utilization for agriculture should be recommended for sustainable agriculture that capable to grant the sustainability in terms of production and friendly environment. To approach the sustainability as mention above, it needs several strategies in swamp land management, including: (1) Detail land resources mapping, (2) Land suitability mapping followed by development of suitable commodities, (3) Soil amelioration and improvement of irrigation net work, (4) Specific location technology development, (5) Improvement and empowerment farm community cappabilities, (6) Infrastructure and agribusiness institution development. The implementation of these strategies needs effective work synchronization and coordination starting from planning towards field work among the related institution, in order to effective works in swamp land management can be reached